2009
DOI: 10.1103/physrevc.80.034002
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive renormalization of the chiral potentials up to next-to-next-to-leading order in higherNNpartial waves

Abstract: We develop a subtractive renormalization scheme to evaluate the P -wave NN scattering phase shifts using chiral effective theory potentials. This allows us to consider arbitrarily high cutoffs in the Lippmann-Schwinger equation (LSE). We employ NN potentials computed up to next-to-next-to-leading order (NNLO) in chiral effective theory, using both dimensional regularization and spectral-function regularization. Our results obtained from the subtracted P -wave LSE show that renormalization of the NNLO potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 46 publications
1
52
0
Order By: Relevance
“…Although the perturbative treatment of WPC does not lead to cutoff independent results, the nonperturbative treatment does seem to fulfill RG invariance [17]. It is …”
Section: Non-vanishing O(q)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the perturbative treatment of WPC does not lead to cutoff independent results, the nonperturbative treatment does seem to fulfill RG invariance [17]. It is …”
Section: Non-vanishing O(q)mentioning
confidence: 99%
“…Note that different approaches towards renormalization of nuclear forces are offered in Refs. [13][14][15][16][17][18], and that perturbative pion theory leads to a very different renormalization program [19].…”
Section: O(qmentioning
confidence: 99%
“…[13] we used subtractive renormalization to calculate S-wave NN phase shifts from O(P 2 ) and O(P 3 ) χET potentials. Here too we found that the phase shifts are not stable once Λ > 1 GeV (see Fig.…”
Section: Figurementioning
confidence: 99%
“…This was accomplished at LO in the work by Nogga et al [40]. At NNLO, the infinitecutoff renormalization procedure has been investigated in [41] for partial waves with total angular momentum J ≤ 1 and in [42] for all partial waves with J ≤ 5. However, for a quantitative chiral NN potential one needs to advance all the way to N 3 LO.…”
Section: Introduction and Overviewmentioning
confidence: 99%